Environmental Protection Against Pollution by Domestic Drain in Uzbekistan - Mahmudova, Dildora; Mashrapov B.O., Master (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2019)
Domestic wastewater is an important, from an environmental point of view, sources of pollution of water bodies in the country. They usually account for up to 30 percent of all wastewater discharged into reservoirs [1].